IMPROVING STUDENTS’ ABILITY TO WRITE ENGLISH DISCOURSE BY MASTERING ITS GLOSSARY IN GRADE XI.MIPA 1 SMAN 1 CIGUGUR - Mohamad Muhtar (Berajah Journal, 2021)
The study aims to determine the extent to which students' ability to write English discourse is increased through mastery of the glossary. Glossary mastery is mastery of vocabularies or terms used in the material to be studied. This is one way for the author to make it easier for students to write an English discourse. This is carried out in hybrid learning during the Covid-19 pandemic. This study uses a classroom action research method with a quantitative approach to 32 students of Class XI.MIPA1 SMAN 1 Cigugur which is carried out in 2 cycles in the odd semester of the 2021-2022 academic year. The results showed that 89% of students were able to write English discourse well. In addition, there was an increase in their writing ability by 27% from their previous ability.